2017
DOI: 10.1371/journal.pone.0180834
|View full text |Cite
|
Sign up to set email alerts
|

MDR1A deficiency restrains tumor growth in murine colitis-associated carcinogenesis

Abstract: Patients with Ulcerative Colitis (UC) have an increased risk to develop colitis-associated colorectal cancer (CAC). Here, we found that protein expression of ABCB1 (ATP Binding Cassette Subfamily B Member 1) / MDR1 (multidrug resistance 1) was diminished in the intestinal mucosa of patients with active UC with or without CAC, but not in non-UC patients with sporadic colon cancer. We investigated the consequences of ABCB1/MDR1 loss-of-function in a common murine model for CAC (AOM/DSS). Mice deficient in MDR1A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Although an inversed correlation between ABCB1 expression and cancer cell growth rate has been commonly known, deficiency in ABCB1 protein expression was shown to result in further restrained tumor growth in colitis‐associated colorectal cancer mouse model, which may be related to change in pathways involved in inflammatory response. 36 In this study, the growth curves obtained from MCTSs also revealed a slightly slower growth rate and less invasive expansion in MDR colon tumor spheroids led by ABCB1 silencing. However, the difference in growth rate was not significant when comparing SW620/Ad300‐ABCB1ko with SW620/Ad300 spheroids, possibly due to less significant involvement of inflammatory mediators in biological activities of SW620/Ad300 cells as the SW620 cell line is not derived from colitis‐associated colorectal cancer tissue.…”
Section: Discussionsupporting
confidence: 56%
“…Although an inversed correlation between ABCB1 expression and cancer cell growth rate has been commonly known, deficiency in ABCB1 protein expression was shown to result in further restrained tumor growth in colitis‐associated colorectal cancer mouse model, which may be related to change in pathways involved in inflammatory response. 36 In this study, the growth curves obtained from MCTSs also revealed a slightly slower growth rate and less invasive expansion in MDR colon tumor spheroids led by ABCB1 silencing. However, the difference in growth rate was not significant when comparing SW620/Ad300‐ABCB1ko with SW620/Ad300 spheroids, possibly due to less significant involvement of inflammatory mediators in biological activities of SW620/Ad300 cells as the SW620 cell line is not derived from colitis‐associated colorectal cancer tissue.…”
Section: Discussionsupporting
confidence: 56%
“…Although CCL12 (MCP-5) shares the same receptor (CCR2) as CCL2, it may have different biological activity than CCL2 [15,16]. CCL12 is a potent monocyte/macrophage chemoattractant, which also attracts lymphocytes and lung fibrocytes [17,18]. In West Nile virus (WNV) infection, CCL12 is significantly upregulated in the brain, which occurs much earlier than the upregulation of IFN-γ and TNF-α and thus is an early trigger of inflammation in the brain [19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the coculture of tumor cells and endothelial cells using a chambered submerged model can be used to study the efficacies of BCG therapy on immune cell proliferation and cytokine secretion 263 . Besides, the chambered submerged model can be used as an in vitro simulation of B cell immunotherapy 303 . Through the utilization of organotypic slice cultures of breast cancer tissue and lymph node tissue, it has been observed that lymph node slices cocultured with tumor slices exhibit greater immunosuppression compared with those cocultured with healthy tissue 274 …”
Section: In Vitro Preclinical Model For Tumor Immunology Investigationmentioning
confidence: 99%
“…270,302,304 A coculture system can be used to simulate remote interactions between tumor cells and immune cells. 263,274,303 For example, the coculture of tumor cells and endothelial cells using a chambered submerged model can be used to study the efficacies of BCG therapy on immune cell proliferation and cytokine secretion. 263 Besides, the chambered submerged model can be used as an in vitro simulation of B cell immunotherapy.…”
Section: Remote Interactionmentioning
confidence: 99%
See 1 more Smart Citation